Scripture and traditions : essays on early Judaism and Christianity in honor of Carl R. Holladay - Gray, Patrick, 1970-; Holladay, Carl R.; O'Day, Gail R., 1954- (Novum Testamentum, Supplements, 2008)
This volume contains twenty-two essays in honor of Carl R. Holladay, whose work on the interaction between early Christianity and Hellenistic Judaism has had a considerable impact on the study of the New Testament. The essays are grouped into three sections: Hellenistic Judaism; the New Testament in Context; and the History of Interpretation. Among the contributions are essays dealing with conversion in Greek-speaking Judaism and Christianity; 3 Maccabees as a narrative satire; retribution theology in Luke-Acts; church discipline in Matthew; the Exodus and comparative chronology in Jewish and patristic writings; corporal punishment in ancient Israel and early Christianity; and Die Judenfrage and the construction of ancient Judaism.